Predicting Efficacy and Dominance in Political Conversations: Impact of Demographic Characteristics - Ting, Su Hie; Sharifah Sophia, Wan Ahmad (Penerbit Akademia Baru, 2017)
In modern democracy, political participation of citizens has liberating outcomes because it is a political system based on representative government. However, there is a widespread political apathy among youths. The study examined the influence of ethnicity and family background in shaping the efficacy and dominance in political conversations of university students. Survey data from 257 students in a Malaysian university were analysed. In the study, the students reported moderate efficacy and dominance in political conversations, of about 60 percent. The results showed that male students have higher efficacy and openness in political conversations than female students. The results also indicated differences by ethnic group in that the Malay and Sarawak and Sabah Indigenous students reported higher levels of efficacy and dominance in political conversations than other ethnic groups. Having family members who are actively involved in politics seem to have some impact on the dominance of the students in political conversations. The findings suggest the family background influences confidence and participation in political discourse.